3-10 GHz noise-cancelling CMOS LNA using gm-boosting technique - Lee, Muyeon; Kwon, Ickjin (IET Circuits, Devices and Systems, 2018)
An ultra-wideband (UWB) low-noise amplifier (LNA) using a 0.11 μm CMOS technology is proposed. The common-gate (CG) input stage for wideband input impedance matching and the common-source (CS) stage for noise cancelling are applied. In the proposed LNA, the current of the CG input stage can be significantly reduced by applying the gm-boosting technique using the noise-cancelling CS stage without additional amplifier, and the noise performance can be improved at the same power consumption. For low-power operation, the LNA consumes 2.9 mW and achieves a noise figure (NF) of S21 between 16.5 and 17.6 dB at S11, lower than -12.4 and 3.6-3.7 dB at frequencies of 3-10 GHz. In low-noise operation, the LNA consumes 8.3 mW, achieving S11 of less than -10.7 dB, S21 of 17.5-18.7 dB, and NF of 2.4-2.9 dB.
Keywords: CMOS technology; Common gates; Common source; Low noise operation; Low-power operation; Noise cancelling; Noise performance; Wide-band input impedance